Nail-patella syndrome with infertility in a 38 year old Saudi male: A case report - Nada Al-Ghamdi (Wolters Kluwer Medknow Publications, 2016)
Nail-patella syndrome (NPS) which also known as hereditary osteo-onychodysplasia is a rare autosomal-dominant disorder characterized by a classic clinical tetrad of changes in the nails, knees, elbows and the presence of iliac horns. Occasionally the central nervous system, the eyes and the renal system are affected. NPS was reported worldwide, affecting males and females equally. Infertility was not mentioned in this syndrome before. Here we are reporting a case of NPS in a 38 year old Saudi male, in association with infertility, which was exceptional and could represent an additional manifestation to the syndrome.